Genetic characterization of a rare case of pheochromocytoma in a pulmonary transplant patient - Parisien-La Salle, Stéfanie; Perreault, Florence; Corbeil, Gilles; Morisset, Julie; Poirier, Charles; Beauregard, Catherine; Räkel, Agnès; Labrecque, Marjorie; Tétreault, Martine; Cohade, Christian; Ferraro, Pasquale; Bourdeau, Isabelle (Frontiers in Endocrinology, 2025)
BackgroundPheochromocytomas (PCCs) and paragangliomas (PGLs) (PPGLs) are rare tumours arising from the chromaffin cells. There is evidence suggesting a link between hypoxemia and PPGLs. Chronic hypoxia can lead to gain of function somatic variants in the EPAS1 gene that encodes for hypoxia-inducible factor 2-alpha (HIF-2α), involved in PPGL tumorigenesis.ObjectiveTo describe a rare case of PCC in a pulmonary transplant patient and characterize the tumour’s genetic background.Clinical CaseA 47 year-old man underwent a lung transplant for chronic obstructive pulmonary disease associated with alpha-1 antitrypsin deficiency. He required home oxygen therapy for 3 years prior to transplant. Nineteen years after transplant, a CT-scan revealed a 5.8 cm x 3.9 cm heterogeneous right adrenal mass (HU of 7). Initial assessments indicated elevated 24-hour urinary catecholamines. Consequently, the patient underwent laparoscopic right adrenalectomy, confirming the PCC diagnosis.Genetic studies1) Germline PPGL multigene panel: After consent, the patient underwent a panel of 14 susceptibility genes for PPGLs that revealed no pathogenic variants. 2) Somatic genetic analysis for EPAS1 gene found no variants. However, tumoral RNA sequencing unveiled activation of the HIF pathway.ConclusionWe describe a rare case of PCC in a pulmonary transplant recipient, with genetic analyses showing no germline pathogenic variants and no somatic variants in the EPAS1 gene. RNA sequencing highlighted HIF pathway activation and angiogenic implications. Further research is necessary to elucidate the genetic and molecular mechanisms underlying PCCs in this specific case and determine its link with hypoxemia in the context of pulmonary disease.